2009
DOI: 10.1592/phco.29.12.1492
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine‐Associated Bradycardia Progressing to Pulseless Electrical Activity: Case Report and Review of the Literature

Abstract: Dexmedetomidine is an alpha(2)-agonist indicated for sedation in critically ill patients and procedural sedation in nonintubated patients. It is a distinctive sedative because it does not cause respiratory depression, but it may cause hypotension and bradycardia. We describe a 74-year-old man who was receiving dexmedetomidine for agitation and experienced progressive bradycardia. The patient experienced a postoperative myocardial infarction 3 days after repair of an abdominal aortic aneurysm. A dexmedetomidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 0 publications
0
39
1
2
Order By: Relevance
“…In previous studies applying single‐ or initial‐dose dexmedetomidine sedation in elderly patients, bradycardia and hypotension were the most common side‐effects, and occurred more frequently with dexmedetomidine doses exceeding 0.5 μg/kg 8, 18, 19, 20, 21. Although a previous study reported that maintenance doses of up to 10 μg/kg per hour were tolerated,27 without producing hypotension or bradycardia, when used as a total intravenous anesthetic agent in certain patients, there are other case reports in which the use of dexmedetomidine in elderly patients was associated with the occurrence of severe bradycardia or hypotension,27, 28 sometimes even progressing to asystole. In our study, none of the patients developed clinically significant hemodynamic disturbances requiring intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies applying single‐ or initial‐dose dexmedetomidine sedation in elderly patients, bradycardia and hypotension were the most common side‐effects, and occurred more frequently with dexmedetomidine doses exceeding 0.5 μg/kg 8, 18, 19, 20, 21. Although a previous study reported that maintenance doses of up to 10 μg/kg per hour were tolerated,27 without producing hypotension or bradycardia, when used as a total intravenous anesthetic agent in certain patients, there are other case reports in which the use of dexmedetomidine in elderly patients was associated with the occurrence of severe bradycardia or hypotension,27, 28 sometimes even progressing to asystole. In our study, none of the patients developed clinically significant hemodynamic disturbances requiring intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Другой группой препаратов, опасных в отно-шении асистолии в ходе операции, считаются цен-тральные α 2 -агонисты (клонидин и дексмедитоме-дин). В отношении последнего препарата есть до-статочно настораживающие публикации [33,34]. Наконец, нам встретилось в литературе сообщение об интраоперационной асистолии после введения во время операции цитостатика адриамицина [35].…”
Section: Discussionunclassified
“…Medicamentos como la dexmedetomidina han demostrado una adecuada respuesta clínica y baja tasa de complicaciones respiratorias, así como menor incidencia de delirium (10)(11)(12)(13)(14) A pesar de los beneficios de dexmedetomidina para sedación, también se ha asociado a eventos adversos graves como bradicardia severa, hipotensión e incluso, paro cardiaco (15)(16)(17). Su uso en diferentes procedimientos, asociados a diferentes modalidades de anestesia tambien se ha visto relacionado con episodios de bradicardia, que requieren de manejo con atropina para la prevención de complicaciones hemodinámicas mas severas (18,19).…”
Section: Introductionunclassified